Building an AI-era healthcare business - Prof. V. E. Adamu; NIF Eneojo (Orapuh, Inc., 2024)
The integration of Artificial Intelligence (AI) into healthcare is revolutionising the industry, providing novel opportunities for businesses to innovate and enhance patient care. This review utilised 35 peer-reviewed, relevant, and current papers written in English, with full texts available from a pool of 365 articles retrieved from PubMed, IEEE Xplore, Google Scholar, ScienceDirect, and Web of Science. This comprehensive review ensures that the included articles are highly relevant, credible, and offer valuable insights into building a healthcare business in the AI era. The article serves as a comprehensive guide for building a successful AI-driven healthcare business, detailing key technologies such as machine learning, natural language processing, computer vision, and robotics. It explores market opportunities, strategic planning, implementation, and future trends. By addressing market needs, navigating challenges, and staying ahead of innovations, businesses can harness AI to transform healthcare delivery. The paper also covers regulatory and ethical considerations, technical and operational challenges, risk management, and strategies for scaling AI solutions. The goal is to provide a structured approach to leveraging AI in healthcare, ensuring improved patient outcomes and operational efficiency.